PENGARUH MODEL COOPERATIVE LEARNING TIPE EXAMPLE NON-EXAMPLE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA - Siti Aisah; Salati Asmahasanah (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2018)
This study aims to find out the learning outcomes of students applying Cooperative Learning model type Example Non Example and using only conventional learning in science subjects class V in MI Tarbiyatusshibyan Bogor, and know how the influence of the implementation of Cooperative Learning model type Example Non Example against science subjects in class V MI Tarbiyatusshibyan Bogor. This research is quantitative descriptive with experimental design